Visualizing intrinsic localized modes with a nonlinear micromechanical array - Sato, M.; Sievers, A.J. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2008)
Micromechanical cantilever arrays provide the opportunity to visualize the nonlinear excitations of a discrete nonlinear system in real time. Both stationary and moving localized nonlinear excitations can be produced either by driving the system at a frequency outside the plane wave spectrum or by driving the system at a frequency within the small amplitude dispersion curve range. To see these modes the tips of the cantilevers are imaged on a 1D CCD camera. The brightness of the image depends on the oscillation amplitude of the cantilever so that a distribution of amplitudes in the array can be recorded as a function of position and time. Both the stationary and traveling excitations have been successfully simulated using a nonlinear lumped element lattice model. The former ILM can appear in any size lattice while the latter requires a low density of modes for the formation of smoothly running excitation.